Trust and loyalty among Islamic and conventional bank customers in Malaysia - Lee, Siew Peng; Moghavvemi, Sedigheh; Lee, Su Teng (Universiti Putra Malaysia, 2019)
The purpose of this study is to explore the dimensions of service quality and test an integrative model to study the influence of service quality, image, and trust on customer loyalty in the Malaysian banking sector. In this study, the service quality model is enhanced to improve the bank’s image. Structural Equation Modelling (SEM) was used to test the proposed research model. The proposed model indicates that delivering high-quality service can result in achieving the well-known image; the result also shows a positive relationship between image and trust, and trust and customer loyalty in both Islamic and conventional banks. Therefore, based on the findings, service quality, bank image and trust are considered to be antecedents of customer loyalty. Bank image is indirectly related to customer loyalty through trust. © Universiti Putra Malaysia Press